Strategic Quality Management and its Impact on Operational Innovation: An Analytical Study at North Refineries Company (International Journal of Financial, Administrative and Economic Sciences, 2026)
This research aims to study the impact of strategic quality management (SQM), with its dimensions (top management commitment, strategic planning, continuous improvement, customer focus, and employee engagement), on operational innovation at North Refineries Company, focusing on its dimensions and importance for strategic leaders in the oil sector. The research is based on the problem: How does strategic quality management affect operational innovation at North Refineries Company? What are the challenges and opportunities for strategic leaders in this regard? The descriptive-analytical approach was used to achieve the research objectives by collecting and mathematically analyzing the responses of the research sample to answer the research hypotheses. The analytical approach employed statistical methods, including a questionnaire and its answers, questionnaire reliability and validity, response distribution, weighted mean, standard deviation, correlation coefficient, simple regression coefficient, and a five-point scale to describe the consistency of the participants' responses. The research sample consisted of 73 leaders. The research yielded several findings and recommendations, the most important of which was the impact of the strategic quality management variable and its dimensions (top management commitment, strategic planning, continuous improvement, customer focus, and employee engagement) on operational innovation at North Refineries Company. A key finding of the research was the necessity of building a culture of quality and innovation, where quality is integrated into the organizational culture, ensuring that employees understand that process innovation is a collective responsibility.
Keywords: Strategic Quality Management; Operational Innovation; North Refineries Company